Polyphenolic Characterization, Antioxidant, and Cytotoxic Activities of Mangifera indica Cultivars from Costa Rica - Mirtha Navarro; Elizabeth Arnaez; Ileana Moreira; Silvia Quesada; Gabriela Azofeifa; Krissia Wilhelm; Felipe Vargas; Pei Chen (Foods, 2019)
The phenolic profile of skin and flesh from Manifera indica main commercial cultivars (Keitt and Tommy Atkins) in Costa Rica was studied using ultra performance liquid chromatography coupled with high resolution mass spectrometry (UPLC-ESI-MS) on enriched phenolic extracts. A total of 71 different compounds were identified, including 32 gallates and gallotannins (of different polymerization degree, from galloyl hexose monomer up to decagalloyl hexoses and undecagalloyl hexoses); seven hydroxybenzophenone (maclurin and iriflophenone) derivatives, six xanthonoids (including isomangiferin and mangiferin derivatives); 11 phenolic acids (hydroxybenzoic and hydroxycinnamic acid derivatives); and eight flavonoids (rhamnetin and quercetin derivatives). The findings for T. Atkins skin constitute the first report of such a high number and diversity of compounds. Also, it is the first time that the presence of gallotannin decamers and undecamers are reported in the skin and flesh of Keitt cultivar and in T. Atkins skins. In addition, total phenolic content (TPC) was measured with high values especially for fruits’ skins, with a TPC of 698.65 and 644.17 mg gallic acid equivalents/g extract, respectively, for Keitt and T. Atkins cultivars. Antioxidant potential using 2,2-diphenyl-1-picrylhidrazyl (DPPH) and oxygen radical absorbance capacity (ORAC) methods were evaluated, with T. Atkins skin showing the best values for both DPPH (IC50 = 9.97 µg/mL) and ORAC (11.02 mmol TE/g extract). A significant negative correlation was found for samples between TPC and DPPH antioxidant values (r = −0.960, p < 0.05), as well as a significant positive correlation between TPC and ORAC (r = 0.910, p < 0.05) and between DPPH and ORAC antioxidant methods (r = 0.989, p < 0.05). Also, cytotoxicity was evaluated in gastric adenocarcinoma (AGS), hepatocarcinoma (HepG2), and colon adenocarcinoma (SW620), with T. Atkins skin showing the best results (IC50 = 138−175 µg/mL). Finally, for AGS and SW 620 cell lines particularly, a high significant negative correlation was found between cytotoxic activity and gallotannins (r = −0.977 and r = −0.940, respectively) while for the HepG2 cell line, the highest significant negative correlation was found with xanthonoids compounds (r = −0.921).